Applying Fiqhiyah Principle " All matters depend on the Intention" and its derivation principle to the acceptable of Intention in thalaq - Aminuddin, Sugeng (2012)
The context of intention in Thalaq needs a dept research due to many cases and ulama difference opinion inside. Instead, most of people don't know and they are not understand which the right syariah is. Actually, they need a simple enlightenment. This research uses an applicable analysis method. It is started from the specific explanation of fiqhiyah principle "All matters depend on the Intention and Its derivation principle, continued with the application of the intention in thalaq. The result of this research is a simple method that is used to know about the rules of intention in Thalaq or when the thalaq can applied be, and all the factors of Thalaq annulments such as victim of magic, a forced people, or drunker. And other causal factor of the acceptable or not this Thalaq application for sick or angry people in conscious condition.